2021
DOI: 10.1101/2021.12.30.474453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preserved T cell reactivity to the SARS-CoV-2 Omicron variant indicates continued protection in vaccinated individuals

Abstract: Importance: The emergence of the highly contagious Omicron variant of SARS-CoV-2 and the findings of a significantly reduced neutralizing potency of sera from convalescent or vaccinated individuals imposes the study of cellular immunity to predict the degree of immune protection to the yet again new coronavirus. Design: Prospective monocentric observational study. Setting: Conducted between December 20-21 at the Santa Lucia Foundation IRCCS. Participants: 61 volunteers (Mean age 41.62, range 21-62; 38F/23M) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Second, when we tested the combined effect of 30 distinct AA substitutions/deletions (mutations found in Alpha, Beta, Gamma and Delta VOCs, of which 10 have also been detected in Omicron), we found that convalescent or vaccinated individuals of Asian origin possess Spikespecific T cells that largely tolerate the combined AA substitutions. These data agree with the recent reports of the substantial, although not absolute, preservation of global Spike-specific T cell response against the highly mutated Omicron [20][21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Second, when we tested the combined effect of 30 distinct AA substitutions/deletions (mutations found in Alpha, Beta, Gamma and Delta VOCs, of which 10 have also been detected in Omicron), we found that convalescent or vaccinated individuals of Asian origin possess Spikespecific T cells that largely tolerate the combined AA substitutions. These data agree with the recent reports of the substantial, although not absolute, preservation of global Spike-specific T cell response against the highly mutated Omicron [20][21][22][23][24][25][26] .…”
Section: Discussionsupporting
confidence: 93%
“…We made the unexpected observation that a large number of T cells (20 out of 35) selected in vitro by PBMC stimulation with whole Spike peptide pool recognized peptides carrying the VOC mutated regions of Spike. This is at odds with ex-vivo results obtained by us and others, since T cells specific for variant regions represent a minority of the global Spike T cell repertoire in the ex vivo analysis 7,[18][19][20][21][22][23][24][25][26] . One might speculate that the in vitro expansion mimics the immunological events occurring after SARS-CoV-2 infection and, as such, the analysis of T cells after in vitro expansion selects for the dominant effector T cell response present during the acute phase of response.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…52 In contrast, several studies found that T cell responses against the Omicron S protein are largely preserved (>80%) in most vaccinated and previously infected adults. 48,[53][54][55][56][57] This lasting cellular immunity is one of many possibilities that contributes to the high (70%) clinical effectiveness of 2 doses of BNT162b2 doses against hospitalization during the initial Omicron wave. 58 Since this study showed that vaccine-induced T cell responses in adolescents are similar to adults, it is likely that their T cell responses remain protective against VOCs, including Omicron.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 , 5 , 6 , 7 However, early data suggest that T-cell responses induced by previous SARS-CoV-2 infection and by the BNT162b2 vaccine are not significantly altered against omicron. 8 , 9 , 10 , 11 , 12 Although these findings suggest that protection against severe SARS-CoV-2 infection with omicron is likely to be better preserved than that against less symptomatic infection in most individuals, the extent of the impact on vaccine effectiveness and potential waning is unclear.…”
Section: Introductionmentioning
confidence: 99%